Predictors of Organizational Commitment among Higher Education Institutions Faculty: Towards A Framework to Enhance Faculty Commitment - Quiambao, Dolores T. (Future Science / FSH-PH Publications, 2023)
This study focused on the predictors of organizational commitment of faculty members in Pampanga so as to serve as inputs for the conception of a framework using a sequential explanatory mixed method approach. The initial phase of the research involved a quantitative analysis to ascertain the factors influencing organizational commitment. These factors were categorized into three groups: personal, professional, and job factors. The personal factors of the study included age, sex, and civil status. The professional factors were divided into educational attainment, length of teaching at the current school and other school(s), while the job factors comprised of salary, benefits, incentives, and job satisfaction. For the 1st phase, 89 faculty served as respondents, while for the 2nd phase, 11 faculty served as participants. Meanwhile, the second part, which was the qualitative phase, selected participants from the same colleges and universities. An Analysis of Variance (ANOVA) was employed to ascertain the relationship between the independent variables and the dependent variable as well as to test hypotheses. The study's results indicate that personal factors and professional factors, namely, length of teaching service and salary, do not have significant effects on organizational commitment. However, incentives and job satisfaction were found to have significant impact on faculty commitment. These results were further confirmed through the qualitative phase, wherein three major themes emerged that connects the results of the quantitative phase namely, job security, organizational self-image, and leadership influence. Higher education institutions may consider the emergent framework as a reference in order to enhance faculty members’ organizational commitment.